Mechanical and Dynamic Properties of Hybrid Fiber Reinforced Fly-Ash Concrete - Dan-Yang Su; Jian-Yong Pang; Xiao-Wen Huang (Advances in Civil Engineering)
In order to explore the influence of basalt-polypropylene hybrid fiber on the static mechanical properties and dynamic compression properties of fly-ash concrete, 16 groups of basalt-polypropylene hybrid fiber fly-ash concrete (HBPC) and 1 group of benchmark concrete were designed and prepared. The slump, static compressive strength, static splitting tensile strength, and dynamic compressive performance tests were tested. At the same time, the mechanism of the mechanical properties of hybrid fiber reinforced fly-ash concrete was analyzed by means of scanning electron microscopy (SEM). The results show that the failure of the benchmark concrete is mainly brittle failure. Compared with the benchmark concrete, the static compressive strength and splitting tensile strength of HBPC are significantly enhanced. Basalt-polypropylene hybrid fiber, polypropylene fiber, and basalt fiber, are extremely significant factors affecting the slump, static compressive strength, and static splitting tensile strength of HBPC, respectively. The peak stress of the benchmark concrete and HBPC increases with the increase of the loading air pressure, showing a certain strain rate effect. SEM shows that the fibers have good dispersibility in the concrete and good adhesion with the concrete matrix interface, but excessive fibers will cause fiber agglomeration, which increases the internal defects of HBPC.